Innovations in Flipping the Language Classroom Theories and Practices (Springer Singapore, 2018)
This book provides advice on flipping from a vast range of topics related to second and foreign language teaching, such as assessment, pronunciation, speaking, listening, reading, writing, and content-based language teaching. Based on insights from other professionals in the field, it helps teachers of English as a foreign language better understand the idea of a flipped classroom. The book provides examples for teachers who wish to start flipping their own classes and additional ideas for those who are already flipping.